Self-reported testing and treatment histories among older Australian men and women who may be at risk of a sexually transmissible infection - Heywood, W.; Lyons, A.; Fileborn, B.; Minichiello, V.; Barrett, C.; Brown, Graham; Hinchliff, S.; Malta, S.; Crameri, P. (C S I R O Publishing, 2017)
© CSIRO 2017. Background: Rates of sexually transmissible infections (STIs) are increasing among older adults in many countries. Little is known about the testing and treatment histories of these populations. Correlates of testing in the past 5 years among older adults who may be at risk of a STI were examined. Methods: A cross-sectional survey of 2137 Australians aged 60+ years that involved questions on STIs and STI testing was conducted in 2015. To help inform potential education campaigns, analyses focused on those who may have been at risk of a STI (n≤805, 38%). Results: Less than one in three reported a STI test in the past 5 years (n≤241, 30%) while 6% (n≤51) reported a STI diagnosis. Those diagnosed typically received treatment from a family doctor or general practitioner. Among men, lower testing rates were associated with older age, identifying as heterosexual, lower educational attainment, not using online dating and reporting one partner in the past 5 years. For women, lower rates of testing were found among those who did not use a condom at their most recent sexual encounter and those with one partner in the past 5 years. Conclusions: STI testing rates were low. This study indicates that consideration should be given to the way targeted education campaigns are formulated, such as emphasising the importance of STI testing to older people who are at risk, as well as encouraging healthcare professionals to discuss sexual health with their older patients.